Pengaruh Derajat Keasaman Yoghurt Dengan Laktobacillus reuteri Prodentis Terhadap Daya Hambat Pertumbuhan Streptococccus mutans Isolat Rongga Mulut Anak (Kajian Secara In vitro ) - , Nirmalinda O Purba ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The competition between plaque bacteria and lactic acid bacteria in difference level of pH can provide information to avoid caries dentis on children. Lactid acid bacteria which is species Lactobacillus reuterion yogurt have bactericidal effect to another bacteria and it is life inpH 3,5 â 8. Probiotics in yogurt that expended on market haverange variation at pH 3-5. Streptococcus mutansone of bacteria that cause caries dentis is life at pH 4-8. The aim of this study is to know the effect from the level of acidity the yogurt use Lactobacillus reuteri Prodentis that can inhibit the growth of Streptococcus mutans. The yogurt made from fermentation acid bacteria Lactobacillus reuteri Prodentis consist of Lactobacillus reuteriDSM 17938 and Lactobacillus reuteri ATCC PTA 5289 that made in many condition of pH 3, 4, 5 and 6. The next, a dilution testing agar was performed with inoculate Streptococcus mutansthat isolated from molar decidui-teeth . Datacollected from diameter inhibition zone of S. mutans. Data was analyzed with Kruskal-Wallisnon parametric testing. The results of analyze was showed average inhibition zone S. mutanshad largest zone in pH 3 ( 7,34 Â± 0,79 mm) and had smallest zone in pH 6 ( 2,02 Â± 0,23 ). Kruskal-wallis test, significantly show pH 3 (p<0,05) inhibit S. mutans growth compared with pH 4,5 and 6. The conclusion from the study show that low pH (L. reuteriProdentis with pH 3) can inhibit S. muttansgrowth. There is no difference of inhibition between yoghurt in pH 4, 5 and 6.